miRNAs in Heart Development and Disease - Lozano-Velasco, Estefania (2024)
Funding Information: This work was supported by funds from the Fundação para a Ciência e a Tecnologia (NETDIAMOND-SAICTPAC/0047/2015), iNOVA4Health-UID/Multi/04462/2020, and LS4FUTURE Associated Laboratory (LA/P/0087/2020) to J.A.B. and funds from the Scientific Employment Stimulus to J.M.I. (Norma Transitória 8189/2018). This work was also support by grants from the Ministry of Education and Science of the Spanish Government to D.F. (PID2022-138163OB-C32) and by a grant-in-aid (CTS-446) of the Junta de Andalucia Regional Council. G.M. was funded by FEDER funds (POCI-01-0145-FEDER-022184), CENTRO 2020 (CENTRO-01-0246-FEDER-000018; CENTRO-08-5864-FSE-000039), and by Fundação para a Ciência e a Tecnologia (UIDP/04501/2020; 2022.01376.PTDC). Publisher Copyright: © 2024 by the authors.